Organizational Climate and Employee Well-Being Correlation at PT Budi Inti Perkasa: Iklim Organisasi dan Korelasi Kesejahteraan Karyawan di PT Budi Inti Perkasa - Ananda Rheza Ardi Pradana Bagaskara Abdul Azis; Widyastuti (Academia Open, 2023)
Background organizational climate significantly influences employees' subjective well-being, a critical factor in organizational success. Specific background in PT Budi Inti Perkasa, understanding this relationship becomes essential to enhance employee satisfaction and productivity. Knowledge gap however, limited studies have examined the correlation between organizational climate and subjective well-being within Indonesian corporate settings, particularly in medium-sized enterprises like PT Budi Inti Perkasa. Aims this study aims to determine the correlation between organizational climate and subjective well-being among 112 employees of PT Budi Inti Perkasa. Results using Spearman's rho correlation analysis, results indicated a significant positive relationship between organizational climate and subjective well-being (p < 0.001), with a moderate effect size (r = 0.357). Novelty this study provides unique insights by employing the saturated sampling technique, allowing for a comprehensive assessment across the entire population of employees. Implications the findings suggest that a supportive organizational climate contributes positively to employees' subjective well-being, which may, in turn, enhance workplace productivity. Highlights: Relationship between organizational climate and employee well-being Significant positive correlation with moderate effect size Implications for enhancing employee satisfaction through organizational climate Keywords: Organizational Climate, Subjective Well-Being, Employee Satisfaction, Spearman Correlation